Information Systems Strategic Planning Using the TOGAF ADM Framework at PT Columbia - Rika Septiana (oneamrd (One a Mllions Dreams Corporation), 2026)
PT Columbia Palembang is a business entity operating in the electronics retail sector, utilizing both cash and credit sales systems. Currently, the company faces significant operational challenges regarding its creditworthiness assessment process, which is still conducted manually; this results in decision-making cycle latency averaging two days. This situation hinders the company's competitiveness in a dynamic market. This study aims to design an enterprise architecture blueprint using The Open Group Architecture Framework Architecture Development Method (TOGAF ADM). The research findings encompass strategic planning that integrates business, data, application, and technology architectures, serving as the foundation for developing a credit-granting Decision Support System (DSS). Implementing this architecture is expected to significantly enhance operational efficiency and the accuracy of credit decisions